The 6 success factors for children with learning disabilities : ready-to-use activities to help kids with LD succeed in school and in life - 4 0 16; 5 Marianne Frostig Center of Educational Therapy (San Francisco : Jossey-Bass, 2009)
Identifies six attributes that contribute to long-term success for children with learning disabilities, including self-awareness, proactivity, perseverance, goal setting, use of social support systems, and emotional coping strategies, and features a selection of related activities, each with a lesson plan, teaching instructions, and reproducible student worksheets.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Education.;Activity programs.;Education. -- Learning disabled children;Special education;Learning disabled children;Learning disabled children;Special education.;Creative activities.;Learning disabled children -- Life skills guides.;Life skills guides; 20; 2